2022
DOI: 10.3390/ijms23136971
|View full text |Cite
|
Sign up to set email alerts
|

The Upregulated Expression of the Citrus RIN4 Gene in HLB Diseased Citrus Aids Candidatus Liberibacter Asiaticus Infection

Abstract: The citrus industry has been threatened by Huanglongbing (HLB) for over a century. Here, an HLB-induced Arabidopsis RPM1-interacting protein 4 (RIN4) homologous gene was cloned from Citrus clementina, and its characteristics and function were analyzed to determine its role during citrus–Candidatus Liberibacter asiaticus (CLas) interactions. Quantitative real-time PCR showed that RIN4 was expressed in roots, stems, leaves and flowers, with the greatest expression level in leaves. Its expression was suppressed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The RPM1 gene has been reported as being upregulated in susceptible citrus genotypes [37], which could be associated with the upregulated expression of the RIN4 gene [45] as these genes have shown to have a positive regulatory interaction [46]. Recently, it was demonstrated that the overexpression of RIN4 aids in the establishment of the CLas infection and the development of HLB symptoms [47].…”
Section: Discussionmentioning
confidence: 99%
“…The RPM1 gene has been reported as being upregulated in susceptible citrus genotypes [37], which could be associated with the upregulated expression of the RIN4 gene [45] as these genes have shown to have a positive regulatory interaction [46]. Recently, it was demonstrated that the overexpression of RIN4 aids in the establishment of the CLas infection and the development of HLB symptoms [47].…”
Section: Discussionmentioning
confidence: 99%